Konsep Nusyuz dalam Mazhab Syafi'i Perspektif Keadilan Gender - Dwi Meitayani (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2010)
The idea of nusyuz in Syafi’i mazhab is interesting because it supports gender equity and can be seen from two perspectives, men and women.